Changing News Use Unchanged News Experiences?. - Costera Meijer, Irene; Groot Kormelink, Tim. (Milton : Taylor & Francis Group, 2021)
Changing News Use pulls from empirical research to introduce and describehow changing news user patterns and journalism practices have beenmutually disruptive, exploring what journalists and the news media canlearn from these changes. Based on 15 years of audience research, the authors provide an in-depthdescription of what people do with news and how this has diversifiedover time, from reading, watching, and listening to a broader spectrumof user practices including checking, scrolling, tagging, and avoiding.By emphasizing people's own experience of journalism, this book alsoinvestigates what two prominent audience measurements - clicking andspending time - mean from a user perspective. The book outlines ways toovercome the dilemma of providing what people apparently want (attentiongrabbingnews features) and delivering what people apparently need (whatjournalists see as important information), suggesting alternative ways toinvestigate and become sensitive to the practices, preferences, and pleasuresof audiences and discussing what these research findings might mean foreveryday journalism practice. The book is a valuable and timely resource for academics and researchersinterested in the fields of journalism studies, sociology, digital media, andcommunication.
Appendix: overview of incorporated research projects 2004-2020 -- Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: News audiences; Online journalism; Journalism -- Technological innovations; LANGUAGE ARTS & DISCIPLINES / Journalism